The Evolution of Colombian Industry in the Context of the Energy-Mining Boom : Symptoms of the Dutch Disease? (2016)
ABSTRACT: This paper seeks to evaluate and demonstrate the hypothesis of deindustrialization and Dutch Disease (DD) for the case of the Colombian economy by using a Beta regression model. The results of the research indicate that it is not possibleto reject the suggestion that the mining and energy boom have potential adverseeffects on the manufacturing sector. RESUMEN: Este artículo busca evaluar y demostrar la hipótesis de la desindustrialización y la enfermedad holandesa (EH) para el caso de la economía colombiana a través de un modelo de regresión beta. Los resultados de la investigación indican que no es posible rechazar la hipótesis de que los auges mineros y energéticos tienen potenciales efectos adversos en el sector manufacturero.